TOWARDS PLAY-BASED LEARNING PRACTICE - Dewi Mulia (Universitas Muhammadiyah Surakarta, 2016)
This paper provides the rationale for an overview and a discussion of the issues that affect best practices for play-based learning, particularly the implicationsof adults’ attitudes regarding child’s play and learning for play-based learning practice in early childhood educational settings in Indonesia. The conceptof play-based learning can be attributed to the National Early Years Learning Framework in Indonesia. However, the practice remains challenging as the result of diverse concepts of child’s play and learning. This discussion begins with an overview of the framework and of government support. It details the relevant research on the challenges that educators and teachers have faced with the implementation of the framework.